2010
DOI: 10.1016/j.jcis.2009.11.071
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion force between cyclopentane hydrates and solid surface materials

Abstract: The mechanisms by which hydrates deposit in a petroleum production line are related to pipeline surface properties, fluid composition and properties, and water cut. In this work, adhesion forces between cyclopentane hydrates and solid surfaces were investigated as a function of the solid material, the presence of water and the presence of petroleum acids in the oil phase. The influence of dissolved water on hydrate adhesion forces was also investigated. The results show that the adhesion force between hydrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
143
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(156 citation statements)
references
References 25 publications
8
143
1
1
Order By: Relevance
“…[17][18][19][20] A few investigations have examined the effect of surface wettability on capillary forces between hydrate particles and surfaces. [21,22] These studies concluded that the deposition of hydrate particles from the fluid bulk onto the pipeline wall is unlikely, because the capillary forces involved are insufficient to maintain adherence of the hydrate particles under flow conditions. However, much higher adhesion forces were reported for hydrates that were grown directly on a surface [21] , indicating that hydrates that form on pipeline walls would likely remain adhered under hydrodynamic forces and providing evidence that their adhesion is governed by forces other than capillary forces.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] A few investigations have examined the effect of surface wettability on capillary forces between hydrate particles and surfaces. [21,22] These studies concluded that the deposition of hydrate particles from the fluid bulk onto the pipeline wall is unlikely, because the capillary forces involved are insufficient to maintain adherence of the hydrate particles under flow conditions. However, much higher adhesion forces were reported for hydrates that were grown directly on a surface [21] , indicating that hydrates that form on pipeline walls would likely remain adhered under hydrodynamic forces and providing evidence that their adhesion is governed by forces other than capillary forces.…”
Section: Introductionmentioning
confidence: 99%
“…4,6,9,[20][21][22][23][24][25] They formed CyC5 hydrate particles by freezing water droplets inside a bath of CyC5 and then brought them into contact with either similarly-formed CyC5 hydrate particles or various solid surfaces. [26][27][28] They used a micro-mechanical adhesion apparatus to measure the adhesion force between previously-formed hydrate particles, 22,26 and/or hydrate and ice particles, with and without the presence of another liquid (e.g.…”
mentioning
confidence: 99%
“…When previously-formed hydrate particles are brought into contact with each other and/or with a desired test substrate, subcooling plays an important role in the adhesion strength that develops between two interacting parts. [23,24,26] It has been shown that the growth rate of hydrates increases as subcooling temperature and/or time increases. [17,35] To investigate the impact of subcooling temperature and time on the hydrate adhesion strength, a solution with χ THF = 0.19 was prepared and used to study formation of THF hydrates on bare and polymer coated substrates (LFG-BL (40 nm)) under various solidification condition.…”
Section: Subcooling Effectmentioning
confidence: 99%
“…[24] The effects of contact force, contact time, and subcooling temperature were investigated in these studies. [23,24,25,26] Hun et al, studied interaction behavior between hydrate particles and water in a temperature-controlled hydrocarbon environment utilizing an apparatus fabricated with a microbalance and z-axis stage. [27] Both groups explained the adhesion forces and trends by a capillary bridge forming between the contacting hydrate particles and/or hydrate particles and liquid droplets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation